Potensi Aktivitas Anti-tirosinase dari genus Citrus: Potensi Aktivitas Anti-tirosinase dari genus Citrus - Arif Ferdian; Khiky Dwinatrana; Relin Yesika (JURNAL FARMASI DAN MAKANAN, 2025)
Skin hyperpigmentation is a common dermatological condition characterized by excessive melanin production, primarily regulated by the enzyme tyrosinase. Natural tyrosinase inhibitors have gained increasing interest as safer alternatives to synthetic depigmenting agents. This study aimed to evaluate and compare the tyrosinase inhibitory activity of peel extracts and solvent fractions of three Citrus species: C. aurantifolia, C. microcarpa, and C. hystrix. Extraction was carried out using Soxhlet and fractionation with n-hexane, ethyl acetate, and methanol. Tyrosinase inhibition was assessed using L-DOPA as the substrate. The results showed significant differences among species and fractions. The n-hexane fraction of C. hystrix exhibited the strongest activity (IC50 34.24 ppm), followed by C. microcarpa (144.05 ppm), while C. aurantifolia showed the weakest inhibitory effect across all fractions. The high potency of C. hystrix is associated with its rich monoterpene content, while lower activity in C. aurantifolia may relate to degradation of thermo-labile flavonoids during Soxhlet extraction. These findings highlight the potential of C. hystrix peel, particularly its non-polar fraction, as a promising natural tyrosinase inhibitor for cosmetic applications.